Common bile duct obstruction associated with platinosoma concinum in cat - Gorgozinho, Katia Barao [UNESP]; Moreira de Souza, Heloisa Justen; Neves, Adriana; de Oliveira, Aline Paula (Soc Medicina Veterinaria Estado Rio de Janeiro, 2007)
Extrahepatic obstruction in cat,can be caused by cholelithiasis, inspissated bile, pancreatic inflammation or fibrosis, duodenal inflammation, bile duct carcinoma or liver fluke infection (Amphimerus pseudofelineus e Platynosomurn concinum). A three-year-old, female neutered siames cat was present with a two-month history of progressive letargy, anorexia and emaciation. She had severe icterus of the mucous membranes, skin, and sclerae. A diagnosis of extrahepataic biliary obstruction was made based on the increased levels of conjugated bilirubin in the serum and the ultrasonography. Hepatic fluke eggs were not diagnosed in the feces because the fibrotic bile ducts were occluded and no eggs were shed into the intestine. Cholecystoduodenostomy was done to relieve posthepatic-biliary obstruction.
Keywords: feline; biliary duct; extrahepatic obstruction